The impact of SARS-CoV-2 infection on immunity reconstitution among pediatric patients after allogeneic hematopoietic stem cell transplantation: a propensity score-matched analysis - Wang, Xin; Liu, LiPeng; Zhang, Luyang; Shang, Yue; Chen, Xia; Ren, Yuanyuan; Liu, Fang; An, Wenbin; Wan, Yang; Li, Xiaolan; Yang, Wenyu; Zhu, Xiaofan; et al. (Frontiers in Pediatrics, 2024)
Background Immunity reconstitution (IR) is crucial for pediatric patients undergoing hematopoietic stem cell transplantation (HSCT), but the impact of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection on lymphocyte subsets post-transplant remains unclear. Therefore, we assessed immune cell dynamics in children after SARS-CoV-2 infection. Methods We enrolled 42 children, including 21 post-HSCT SARS-CoV-2 infected and 21 matched, non-infected historical controls (1:1 matching based on propensity scores). The time from HSCT to SARS-CoV-2 infection in the infected group was determined by the beginning of follow-up for the non-infected group. The primary endpoint was 270-day IR kinetics post-infection. Results Our findings showed similar recovery trends between the infected group and non-infected group both in UCB and HID recipients. In the UCB cohort, the NK cell reconstitution in the infected group was poorer compared to the non-infected group, but this difference did not reach statistical significance (P = 0.178). Furthermore, HID transplantation might be a trend towards poor CD19+ T-cell reconstitution [hazard ratio (HR): 0.43, 95% CI: 0.18–1.04, p = 0.06]. No statistically significant difference was observed in terms of secondary infections across the UCB (P = 0.150) and HID (P = 0.980) cohorts as well as there was no discernible difference in overall survival between the two groups (P = 1). Conclusions Our analysis reveals that SARS-CoV-2 might temporarily impaired the IR process in the short term, with recovery to a comparable trend as observed in non-infected patients approximately 9 months post-infection.